2015
DOI: 10.3892/ol.2015.3311
|View full text |Cite
|
Sign up to set email alerts
|

Pleural synovial sarcoma patient treated with combined chemotherapy and Endostar, plus sunitinib maintenance therapy: A case report and review of the literature

Abstract: Synovial sarcoma is a rare, highly malignant soft-tissue tumor that occurs primarily in the extremities. At present, there is no effective clinical treatment for this condition. The present study reports the case of a 49-year-old male who was diagnosed with pleural synovial sarcoma and treated with recombinant human endostatin (Endostar) combined with chemotherapy for a total of six cycles, followed by sunitinib maintenance therapy. To the best of our knowledge, this is the first reported use of sunitinib for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The results show that Endostar combined with chemotherapy result in a higher CBR and a longer median PFS in the patients with advanced sarcoma (8.6 months versus 4.4 months), with tolerable toxicity, which are consistent with previous reports of endostar combined with chemotherapy in other solid tumors [2628]. In our study, the PFS of the combined group is significantly longer than that of the control group.…”
Section: Discussionsupporting
confidence: 92%
“…The results show that Endostar combined with chemotherapy result in a higher CBR and a longer median PFS in the patients with advanced sarcoma (8.6 months versus 4.4 months), with tolerable toxicity, which are consistent with previous reports of endostar combined with chemotherapy in other solid tumors [2628]. In our study, the PFS of the combined group is significantly longer than that of the control group.…”
Section: Discussionsupporting
confidence: 92%
“…(18) Since then, few cases have been reported by others. (17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) A range of treatments have been suggested for pleural synovial sarcoma including extensive surgical resection, (neo)adjuvant chemotherapy (with ifosfamide and doxorubicin), and radiotherapy. (19,(24)(25)(26)(28)(29)(30)(31) Complete surgical resection appears to be associated with improved survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of advanced bone and STSs, Endostar combined with chemotherapy had significant activity toward increasing PFS and improving the clinical benefit rate 11. Teng et al reported that the treatment of a pleural synovial sarcoma patient with combined chemotherapy and Endostar plus sunitinib was effective 12. A retrospective case series study with a total of 71 patients suffering from advanced STSs suggested that Endo-star combined with chemotherapy had a higher disease control rate and longer PFS than traditional chemotherapy 13…”
Section: Discussionmentioning
confidence: 99%